Impact of a formal pharmacist-run oral antineoplastic monitoring program: A pilot study in an adult genitourinary oncology clinic. (June 2019) - Conliffe, Brette; Figg, Lindsay; Moffett, Padmini; Lauterwasser, Leslie; Parsons, Laura Beth
Background: In recent years, there has been a changing paradigm in the management of oncologic disease states from the use of intravenous therapies, requiring a visit to the infusion center or hospitalization, to new therapies that can be administered orally. 1, 2 Several publications have evaluated the role pharmacists may play in the initial prescribing of oral chemotherapy, however the impact of a formalized pharmacist follow-up program has not been well defined. This study evaluates the impact of a pilot pharmacist-run oral antineoplastic monitoring program. Methods: This retrospective cohort analysis evaluated patients prescribed an oral antineoplastic in the genitourinary oncology clinic at an academic medical center between 1 July 2014 and 15 March 2017. Patients enrolled in the program were compared to a historical control group. The primary objective was adherence to pre-defined standards for monitoring. Secondary objectives include persistence on therapy, need to seek medical care, analysis of pharmacist interventions, patient satisfaction, and financial impact for the on-site retail pharmacy. Results: In total, 33 patients were evaluated (11 cases, 22 controls). Average adherence to monitoring recommendations was significantly higher in the case group compared to controls (89% vs. 61%; p = 0.008). In total, 67 interventions were made by the clinical pharmacist with an average of 6 per patient. Conclusions: This study shows that formalized pharmacist follow-up programs can improve patients' adherence with antineoplastic monitoring standards. Additionally, pharmacists made clinically significant interventions and had high patient satisfaction, providing justification for expansion into other disease states.